Legal Due To The Party Layoff Due To Covid 19 - Muhammad Danial Ar Rasyiid; Habib Adjie (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Indonesia became one of the countries infected with Covid-19. This certainly has an impact that can harm the country and society. Therefore, the government issued a policy of Large-Scale Social Restrictions (PSBB) with the aim of deciding the spread of Covid-19. One of the impacts felt by the community with the presence of Covid- 19 is the Termination of Employment (FLE) carried out by several companies to workers on the grounds of force majeure or loss. This reasoning is controversial, bearing in mind that force majeure cannot be said to be a reason that can cause harm as in the Covid-19 outbreak, and is deemed to deviate from Article 164 Paragraph (3) of Law Number 13 Year 2003 concerning Labor.